Body-centric Wireless Communication (BCWC) Application Microstrip Patch Antenna - Singh, Jaget (International Journal of Computer Sciences and Engineering, 2019)
In this paper a simple and light weight microstrip patch antenna has been presented. This antena is designed on a FR-4 substrate with dielectric constant of 4.3 and 1.6 mm thickness. The designed antenna is simmulated and anyalized for Body-centric Wireless Communication (BCWC) application, which operates at 5.126 GHz Industrial, Scientific and Medical (ISM) Hyper Local Area Network (LAN) band. Antenna is designed with dimensions of 13.2x18.6x1.6 mm3. A parametric study has been carried out which shows a return loss of -31 dB and gain of 3.8 dBi at the designed frequency. The software used for simulation of this antenna is IE3D HyperLynx Zeland. A probe fee is used to excite the antenna.